Identification of Worm Types that Infest Bali Cattle in Bolo District - Kuntum Khoirani; HY Lukman; Nikmaturrayan Nikmaturayan; Hosin Hosin (Hasanuddin University, 2020)
Bali cattle are the primary genetic resources of Indonesia. Besides beef cattle are used as breeds, they are also distributed to all regions in Indonesia. One of the requirements for good quality of beef cattle is to be free from parasitic diseases. Bima Regency is one of the areas of Bali cattle population centers in West Nusa Tenggara, but the Bali cattle maintenance system in Bima Regency is generally still extensive, certainly increasing the potential for diseases. The disease can cause economic losses, disrupt the health of livestock and the health of people who consume meat derived from parasitic-infected animals. This study used 50 stool samples of Bali cattle aged 5 to 12 months taken randomly. The sedimentation and flotation method was used to identify nematode worm eggs. The parameters observed were gastrointestinal parasitic morphology, and then the data were analyzed descriptively. It was found two types of parasites that infected bali cattle in Bolo Sub-district, Ascaris spp, and Trichuris sp. As caris spp infected as many as 72% of 50 bali cattle faecal samples, 72% were infected by Trichuris sp., and mixture of Ascaris spp and Trichuris spp infected 54 % of the sampled cattle. The improvement of cage management and cattle maintenance system are necessary to implement. Those are by taking into high-quality nutrition feeding, regular anthelminthic treatment, and avoiding the feeding of green forage to avoid worm infection and re-infection.